ENHANCING STOCK MARKET AWARENESS: A KEY TO FINANCIAL LITERACY AND ECONOMIC GROWTH - M. V., Malini; S., Savitha; K., Aswathanarayana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Stock market awareness is a crucial aspect of financial literacy and a significant driver of economic growth. This paper examines the multi-dimensional importance of stock market awareness and its profound impact on individual financial behaviors and the broader economic framework. It discusses the need for comprehensive educational programs, the influence of government policies, and the pivotal role of financial institutions in encouraging public participation. The study identifies major challenges such as financial illiteracy, misinformation, and perceived risks while proposing forward-looking strategies to overcome these barriers. It advocates leveraging technological advancements, enacting policy reforms, and promoting public-private partnerships to build a sustainable model for enhancing stock market awareness. This paper suggests that an informed public will lead to increased market participation, improved capital allocation, and a more resilient financial system that fosters sustainable economic growth.